2012
DOI: 10.1007/s10633-012-9318-1
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of central visual function following steroid pulse therapy in acute zonal occult outer retinopathy

Abstract: The purpose of this study was to report a patient with acute zonal occult outer retinopathy (AZOOR) unilaterally, who received steroid pulse therapy. A 42-year-old woman presented with photopsias and severe vision loss in her left eye. Visual acuity was 0.04, and Humphrey visual field testing showed overall depression with a mean deviation (MD) value of -25.78 dB in the left eye. Fundus and angiographic examinations found no specific abnormal findings, leading to a diagnosis of AZOOR. Optical coherence tomogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 8 publications
2
19
0
Order By: Relevance
“…Our OCT findings were similar to those previously reported for other AZOOR patients [3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15]. It has been reported that the natural course of AZOOR is varied [1, 2].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our OCT findings were similar to those previously reported for other AZOOR patients [3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15]. It has been reported that the natural course of AZOOR is varied [1, 2].…”
Section: Discussionsupporting
confidence: 91%
“…There have been several detailed reports about AZOOR patients who showed morphological and functional improvements in their visual function [4, 8, 9, 10, 11, 12, 13, 14, 15]. Spaide et al [4] reported restoration of the IS/OS line in the improved areas of the visual field, but electrophysiological alterations of these patients were not demonstrated in the report.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Some experts feel that AZOOR is a unique entity that may be more precisely defined by multimodal imaging: 1) autofluorescence, demonstrating characteristic zonal degeneration of the outer retina and RPE, typically beginning around the nerve and progressing to the periphery, and 2) high-definition spectral domain OCT, showing zonal or annular loss of the photoreceptor layer and IS/OS complex. 81,143,184,199,263,267 5.2.…”
Section: Acute Zonal Occult Outer Retinopathymentioning
confidence: 99%